2021
DOI: 10.1016/j.eti.2020.101291
|View full text |Cite
|
Sign up to set email alerts
|

Phenol-rich bio-oil derivation via microwave-induced fast pyrolysis of oil palm empty fruit bunch with activated carbon

Abstract: In the present study, oil palm empty fruit bunch (EFB) was subjected to microwaveinduced fast pyrolysis. It has been demonstrated that EFB pyrolysis with activated carbon (AC) as microwave susceptor significantly increases the bio-oil yield (38.26 wt%) at an optimized temperature of 500 •C as compared to the EFB pyrolysis without AC (1.89 wt%). The EFB bio-oil produced at 500 •C (EPO500) was characterized to be enriched with oxygenated compounds (92%) and high nitrogenous compounds (8%) with an overall low car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…In Fig. 4, an example of comparison of ultimate analyses of the chosen samples with other studies is shown [35,[44][45][46][47][48][49][50][51][52]. In all of the works, there is a little difference in the ultimate analytical results of the feedstock samples.…”
Section: Composition (%)mentioning
confidence: 84%
See 1 more Smart Citation
“…In Fig. 4, an example of comparison of ultimate analyses of the chosen samples with other studies is shown [35,[44][45][46][47][48][49][50][51][52]. In all of the works, there is a little difference in the ultimate analytical results of the feedstock samples.…”
Section: Composition (%)mentioning
confidence: 84%
“…3 [35,[44][45][46][47][48][49][50][51][52]. All of the works show a minor difference in the proximate analysis results of the feedstock samples.…”
Section: Composition (%)mentioning
confidence: 92%
“…They found that a large specific surface area of the AC can increase both yield and quantity of bio-oil. Idris et al (2021) studied microwave-induced fast pyrolysis of oil palm empty fruit bunches (EFB) with added AC. They found that AC as a MW absorber significantly increased the bio-oil yield to 38.3 wt% at 500 °C and phenol compounds to 43.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activation involves carbonization followed by activation using carbon (IV) oxide (CO 2 ) or steam (H 2 O), while chemical activation involves using one of the reagents as an activating agent [14]. Thus, the chemical activation process is an efficient method to produce activated carbon with a high surface area and a distributed porosity [15]. Thus, co-pyrolysis of biomass substrate…”
Section: Introductionmentioning
confidence: 99%